Analysis of the Length of Waiting Time for Outpatient Services at BPJS FMC Hospital in October - December 2024 - Renata; Christin Angel; Anthonius Christopher Wisnu; Erihka Silvia Siregar (CV. Publikasi Indonesia, 2025)
This study aims to analyze the waiting time for BPJS outpatient services at FMC Bogor Hospital from October to December 2024. Employing a quantitative approach, data collection was conducted through direct observation, interviews with hospital staff, and documentation of patient waiting times from registration to the receipt of medical services. The findings indicate that the average waiting time for BPJS outpatients at FMC Bogor Hospital is 45 minutes, which exceeds the standard set by BPJS Kesehatan, namely 30 minutes. Several factors contribute to this prolonged waiting period, including high patient volumes, limited availability of medical personnel, and inefficiencies in administrative procedures. These conditions not only affect operational performance but also influence patient satisfaction. Based on the analysis, this study recommends improvements in patient flow management, increasing the number of medical staff, and implementing information technology systems to streamline administrative processes. These efforts are expected to optimize service efficiency and enhance the quality of healthcare delivery, particularly for BPJS participants relying on timely and accessible medical treatment.